Nötrofil lenfosit oranı daha yaygın, ciddi, kompleks koroner arter hastalığı ve miyokart perfüzyonunda bozulma ile ilişkilidir - Ekrem Şahan; Suzan Polat (KARE Publishing, 2014)
Firstly I will thank M.D. Aslı Tanındı and her friends for their publication named "Neutrophil to lymphocyte ratio is associated with more extensive, severe and complex coronary artery disease and impaired myocardial perfusion". The relationship between neutrophil to lymphocyte ratio and the mortality - morbidity of stable coronary artery disease and acute coronary syndromes is described in this study and other studies. I have some thought to add to the discussion part about this article.